2001
DOI: 10.1116/1.1372915
|View full text |Cite
|
Sign up to set email alerts
|

Field-emission properties of vertically aligned carbon-nanotube array dependent on gas exposures and growth conditions

Abstract: We grew vertically aligned carbon nanotubes ͑CNTs͒ using microwave plasma-enhanced ͑MPE͒ and thermal chemical-vapor deposition ͑CVD͒ and characterized their field emission properties. We observe that the flickering and instability in the field emission are due to the metal particles present on the field-emission array ͑FEA͒ surface, particularly from the MPECVD-grown samples. The existence of metal particles is an obstacle to obtaining reliable emission properties. The emission properties of the CNT-FEA are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Their work also confirmed that an F-N transition of with the nonlinearity resulted from thermionic emission (TE) at low electric field to field emission (FE) at high electric field, which was also observed in our work, both for DLC and p-DLC films. But at the relatively low electric field, field emission mechanism of p-DLC film was different from that of DLC film, and the similar F-N plot could also be observed in vertically aligned CNTs [26]. Although phosphorus incorporation could improve the field emission performance of the DLC films, the mechanism of field emission was still debatable.…”
Section: Resultsmentioning
confidence: 97%
“…Their work also confirmed that an F-N transition of with the nonlinearity resulted from thermionic emission (TE) at low electric field to field emission (FE) at high electric field, which was also observed in our work, both for DLC and p-DLC films. But at the relatively low electric field, field emission mechanism of p-DLC film was different from that of DLC film, and the similar F-N plot could also be observed in vertically aligned CNTs [26]. Although phosphorus incorporation could improve the field emission performance of the DLC films, the mechanism of field emission was still debatable.…”
Section: Resultsmentioning
confidence: 97%
“…due to high local currents at the tips of the MWCNTs [19,[28][29][30] in the SEM vacuum chamber during FE as shown in Figures 4(a) and 5(a). A flash heating the emitter at about 1300 K allows the molecules to be desorbed, and the nanotube emitter recovers the original clean surfaces [30].…”
Section: Resultsmentioning
confidence: 99%
“…Both of them contribute to the beak of the MWCNT, although Refs. [26,28,29] provide data that the oxidisation is a negative effect on the FE current and the stability. At present, we think both of them are important to the same extent for the FE stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the measurements of field emission from CNT pertain to the dc characteristics of films (Zhu et al, 1999), arrays (Lim et al, 2001), and composites (Wang et al, 1998), which only provide a statistical evaluation of the properties with large numbers of CNT. Furthermore, the electric field, and thus the total emitted current, is reduced when the CNT are close together (Hii et al, 2006).…”
Section: Carbon Nanotubes 436mentioning
confidence: 99%